Intercultural Interaction in the Multiethnic Context of Makassar City: A Case Study in an Urban Neighborhood - Arifin, Iqbal; ., Asmunandar; Paramitha Darmayanti, Dyan (KnE Social Sciences, 2024)
This research is a case study in an urban environment that investigates intercultural interaction in the multiethnic context of Makassar City. The research aims to understand how intercultural interactions occur in the daily lives of the residents of Makassar, which is a city rich in cultural and ethnic diversity. Data were collected through direct observation and in-depth interviews. Seven local residents with diverse ethnic backgrounds were selected as informants for this study. Intercultural communication, acceptance and tolerance, cooperation and collaboration, the influence of intercultural interaction, and challenges and barriers are some of the elements studied. According to the results of the study, intercultural communication in Makassar City requires the use of language and special signs to overcome language differences. The majority of Makassar City residents appreciate and accept ethnic diversity. However, there are still problems in overcoming differences in tradition and culture. In various initiatives and activities involving multiethnic communities, there is cooperation and collaboration between ethnicities. The social, cultural, and economic life of Makassar City is greatly enhanced by intercultural interaction. However, there are some challenges faced, such as language differences and cultural stereotypes, which can make inter-ethnic communication and understanding difficult. This study enhances our understanding of cultural interaction in a multiethnic urban environment and offers suggestions for improving inter-ethnic understanding, tolerance, and collaboration in Makassar City. Keywords: intercultural interaction, multiethnicity, urban environment